2010
DOI: 10.1099/jmm.0.017285-0
|View full text |Cite
|
Sign up to set email alerts
|

A rhesus macaque (Macaca mulatta) model of aerosol-exposure brucellosis (Brucella suis): pathology and diagnostic implications

Abstract: The US Centers for Disease Control and Prevention lists Brucella as a potential bioterrorism threat requiring enhanced diagnostic capacity and surveillance (http://emergency.cdc.gov/bioterrorism/). Successful treatment and management of patients after exposure to biological threat agents depends on accurate and timely diagnosis, but many biothreat agents present with similar, vague clinical signs – commonly referred to as ‘flu-like illness’. Diagnosis of brucellosis is notoriously challenging, especially early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 13 publications
5
23
0
Order By: Relevance
“…An adverse effect of brucellosis on the liver in the current study was supported by positive liver biopsies, liver tissue burdens, and microscopic observations of hepatocellular necrosis. In addition to a limited change in clinical pathology parameters, a limited effect on clinical hematology parameters was observed in the B. suis aerosol-challenged acutely infected RMs (24). This is consistent with the results from the current study.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…An adverse effect of brucellosis on the liver in the current study was supported by positive liver biopsies, liver tissue burdens, and microscopic observations of hepatocellular necrosis. In addition to a limited change in clinical pathology parameters, a limited effect on clinical hematology parameters was observed in the B. suis aerosol-challenged acutely infected RMs (24). This is consistent with the results from the current study.…”
Section: Discussionsupporting
confidence: 92%
“…The changes observed in clinical pathology and hematology parameters in this study were consistent with human brucellosis, in which the majority of clinical pathology indicators are indistinct (24). In addition, a recent study observed limited changes in clinical pathology parameters in RMs that were monitored for 7 days after challenge (acute infection) with a high dose of 5.60Eϩ08 CFU B. suis (24).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations